Shoulder joint replacement can improve quality of life and outcome in patients with dysmelia: a case series - Merkle, Tobias Peter; Beckmann, Nicholas A.; Bruckner, Thomas; Zeifang, Felix (BMC musculoskeletal disorders, 2016)
Arthroplasty is a proven treatment option for glenohumeral osteoarthritis. Common indications include primary or posttraumatic osteoarthritis, avascular necrosis of the humeral head, rotator cuff tear arthropathy and rheumatoid osteoarthritis. Arthroplasty is rarely performed among patients with glenohumeral dysmelia. An overuse of the upper limb in patients with thalidomide-induced phocomelia and people with similar congenital deformities like dysmelia results in premature wear of the shoulder joint. This study aims to evaluate our experience with cases of glenohumeral osteoarthritis caused by dysmelia and treated with arthroplasty. To date, few reports on the outcome of shoulder arthroplasty exist on this particular patient group.